PENGEMBANGAN LEMBAR KERJA SISWA (LKS) PRAKTIKUM BERBASIS INKUIRI TERBIMBING PADA MATERI LARUTAN PENYANGGA DI SMA NEGERI 4 SUNGAI RAYA - Wiji Tri Utari; Raudhatul Fadhilah; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2018)
This research aimed to develop student worksheet for experiment based on guided inquiry in buffer solution at SMA Negeri 4 Sungai Raya which are valid, practical, and effective. The development of student worksheet in this research used Borg & Gall model. The results of this research showed that : (1) This student worksheet was stated as a valid result with an average score 1,00 which classified very high criteria. (2) This student worksheet was stated as a practical result with the percentage of preliminary field testing was 83,71% and 85,65% in main field testing which classified very high criteria. (3) This student worksheet was stated as an effective result with the classical completeness percentage was 76,47%. Based on the results, it can be concluded that the worksheet for experiment based on guided inquiry can be used in learning process.Keywords: Guided Inquiry, Buffer solution, Student worksheet for experiment.